Poly(3-hydroxybutyrate) and Poly(3-hydroxybutyrate-co-3-hydroxyvalerate): Structure, Property, and Fiber - Qingsheng Liu; Hongxia Zhang; Bingyao Deng; Xiaoyan Zhao (International Journal of Polymer Science)
Poly(3-hydroxybutyrate) [P(3HB)] and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] are produced by various microorganisms as an intracellular carbon and energy reserve from agricultural feedstocks such as sugars and plant oils under unbalanced growth conditions. P(3HB) and P(3HB-co-3HV) have attracted the attention of academia and industry because of its biodegradability, biocompatibility, thermoplasticity, and plastic-like properties. This review first introduced the isodimorphism, spherulites, and molecular interaction of P(3HB) and P(3HB-co-3HV). In addition, the effects of 3HV content on the melting temperature and crystallization rate were discussed. Then the drawbacks of P(3HB) and P(3HB-co-3HV) including brittleness, narrow melt processing window, low crystallization rate, slow biodegradation rate in body, and so on were summarized. At last, the preparation, structure, and properties of P(3HB) and P(3HB-co-3HV) fiber were introduced.